"Shock" Septic: Clinical experience in Obstetrics and Gynecology - Gonzales Enders, Rodolfo (2015)
Twenty-six cases of patients who developed septic shock and who were diagnosed and treated according to a pre-set pattern is studied. Septic abortion importance as the leading cause of septic shock stresses. Negative microorganisms Klebsiella-Aerobacter and Escherichia coli. Emphasis is given to the importance of a therapeutic regimen based on the pathophysiology of shock, including a variable apmplitud surgical treatment, but applied early, in order to eliminate the infectious focus.